Cervical amoebiasis mimicking cervical carcinoma: A rare presentation of a common infection - Arvind Ahuja; Minakshi Bhardwaj (Elsevier, 2016)
Summary: Cervical amoebiasis is an extremely rare diagnosis with only a small number of published case reports. This disease may present as cervical growth mimicking cervical carcinoma. Owing to the similarity of the clinical presentation of bleeding per vagina and per speculum examination showing growth or ulcers, definitive diagnosis is made on microscopic examination only. We present a rare case of cervical amoebiasis in a 28-year-old, multiparous female who presented with a history of vaginal bleeding. The patient was treated with metronidazole and diloxanide furate, after which she recovered. Awareness of this rare entity is important for clinical suspicion and for the pathologist to identify trophozoites and make a diagnosis, preventing unwarranted investigations. Accurate diagnosis also facilitates quick management of a patient; as this disease is an infective pathology that can easily be treated by antibiotics. Keywords: Amoebiasis, Cervix, Carcinoma, Vaginal bleeding